MEMBERANTAS SUAP DI DALAM LEMBAGA PEMASYARAKATAN SUKAMISKIN BANDUNG - Surya Darma; Deny Haspada (Program Studi Magister Ilmu Hukum Pascasarjana Universitas Langlangbuana, 2019)
The State of Indonesia is a state of law as stated in the 1945 Constitution Article 1 Paragraph (3), this provision means that all people are treated equally before the law (equality before the law). Law enforcement is getting better by not knowing indiscriminately for Actors who commit violations of the law, thus what has been done by law enforcement officials makes the face of Indonesian law enforcement even better. The core meaning of law enforcement conceptually lies in the activity of harmonizing the relationships of values ​​that are set out in the rules and attitudes of action as a series of translation of the final stage of values, to create, maintain and maintain peaceful social relations. Conception that has a philosophical basis, requires further explanation, so that it will look more concrete.